The effectiveness of liver transplantation in reducing lipid levels in Saudi children with homozygous familial hypercholesterolemia - Al-Ashwal, Abdullah; Al-Mansour, Salman; Al-Shagrani, Mohammed; Al-Gofi, Talal; Broering, Dieter; Alhuthil, Raghad (Frontiers in Cardiovascular Medicine, 2024)
IntroductionThe lipid profiles of patients aged <15 years who have been diagnosed with homozygous familial hypercholesterolemia (HoFH) at King Faisal Specialist Hospital & Research Center (Riyadh) were examined.MethodsThe total cholesterol and low-density lipoprotein cholesterol (LDL-C) levels of 17 patients were measured on initial presentation and compared with the levels measured after pharmacological treatment and then again after liver transplantation.ResultsAt the end of the pharmacological treatment, the total cholesterol levels decreased by an average of 3.79 mmol/L (reduced by 15.40%) (P < 0.001), and LDL-C levels decreased on average by 2.73 mmol/L (reduced by 13.46%) (P = 0.014). However, in two patients, LDL-C levels increased by 5.42% and 9.03% after pharmacological treatment. Conversely, the lipid values measured after liver transplantation decreased significantly nearly to within normal and borderline limits. The post-transplant total cholesterol and LDL-C levels declined by a mean of 19.96 mmol/L (reduced by 81.04%) and 17.47 mmol/L (reduced by 84.27%), respectively (P < 0.001 for both).DiscussionThese findings suggest that liver transplantation provides a more effective means to reduce elevated total cholesterol and LDL-C levels in patients with HoFH. Although liver transplantation is considered a better treatment for FHoH, risks, complications, and donor organ shortage may present problems.